English language use of the Malaysian Tamil diaspora - Krishnan, M. Raadha; Sharmini, Sharon (Taylor and Francis, 2021)
Diasporic Indian languages in Malaysia are unique and distinguishable from their native variants. Past studies have indicated that dominant languages tend to overpower minority languages in multilingual communities, hence causing languages to shift. The aims of this study are to identify the language choices of Malaysian Tamils and to what extent does English influence their shift from their native language. The respondents were 30 Malaysian Indians. The findings of the study revealed that in the family domain, there was an alarming shift to English when participants spoke to their children (93%) and their spouses (63%) as opposed to the older generations. Meanwhile, in the friendship domain, 76% of the participants preferred using English when they had to speak to other Malaysian Tamils. As for strangers, there was a 50–50 distribution between English and Malay between these participants. These findings seem to show that most families shifted from their native language to English among children in the family domain, education domain and friendship domain. Therefore, it is possible to note that factors such as imperialism, economic status and relevance of usage in language domains are the driving factors behind the shift of Tamil to English in Malaysia.